Usability of fluorescence angiography with indocyanine green in the surgical management of penetrating abdominal trauma: A case series. (March 2021) - Osterkamp, Jens T.F.; Patel, Mohamed Q.; Steyn, Elmin; Svendsen, Lars-Bo; Forgan, Tim; Achiam, Michael P.
Abstract: Background: The surgical management of penetrating abdominal trauma can be challenging, and despite improvements in diagnostics and treatment, mortality and morbidity rates remain high. Intraoperative fluorescence angiography with indocyanine green (ICG-FA) is currently implemented in many elective surgical settings. However, there are few data regarding the usability of ICG-FA in emergency surgery, and to our knowledge, ICG-FA has not been evaluated in penetrating abdominal trauma. Hence, our objective was to determine the feasibility and usability of ICG-FA in surgical management of penetrating abdominal trauma. Materials and methods: A total of 20 patients undergoing emergency laparotomy for penetrating abdominal trauma were included. The usability of ICG-FA was evaluated using the System Usability Scale (SUS®). The intraoperative macroscopic assessment was compared with that using ICG-FA, and any influence of ICG-FA on surgical management was documented. Results: The ICG-FA was completed in all cases and rendered a "good" median SUS® score of 68.8 (interquartile range, 60.6–82.5) by first-time users. The use of ICG-FA influenced surgical management in 14 cases (70%). In six of those cases, ICG-FA significantly changed surgical management. There were no postoperative complications related to surgical management. Conclusion: ICG-FA proved useable and relevant in the setting of penetrating abdominal trauma. Although this was only a small case series, the study showed that ICG-FA could substantially influence surgical management of penetrating abdominal trauma, adding considerable patient benefit. Highlights: A novel study on the usability of fluorescent guided surgery with Indocyanine green (ICG-FA) in abdominal trauma. ICG-FA proved useable and clinically relevant in the setting of penetrating abdominal trauma. ICG-FA substantially influenced surgical management, adding patient benefit, in a majority (70%) of cases.